Anticonvulsant activity of ethanol extracts of Vetiveria zizanioides roots in experimental mice. (17th July 2013) - Gupta, Ritu; Sharma, Krishan Kant; Afzal, Muhammad; Damanhouri, Zoheir A.; Ali, Babar; Kaur, Rupinder; Kazmi, Imran; Anwar, Firoz
Abstract: Context: Vetiveria zizanioides Linn. (Gramineae), an aromatic plant commonly known as vetiver, is traditionally used for various ailments. Ethanol and aqueous extract of this plant found extensive use in Indian folklore medicine and used in treatment of a wide range of disorders including seizure. However, the anticonvulsant activity of this plant has not been studied. Objective: To evaluate anticonvulsant activity of ethanol extract of V. zizanioides (EEVZ) in experimental mice. Materials and methods: Anticonvulsant activity of EEVZ was determined by maximal electroshock stimulation (MES) and pentylenetetrazole (PTZ) in mice for 8 d experimental protocol. The extract at a dose of 100, 200 and 400 mg/kg body weight was administered once by oral route. Results: LD50 value of EEVZ in mice was found at a dose of 600 mg/kg body weight. EEVZ at a dose of 400 mg/kg significantly ( p  < 0.001) reduced flexion (l5.98 to 3.73 s), extension (13.73 to 0.96 s), clonus (14.07 to 4.93 s), stupor (6.29 to 1.22 s) in the MES model. Further, it increases onset of clonic (88.25 to 708.32 s/30 min) and tonic (139.52 to 1126.39 s/30 min) in the PTZ model. In the PTZ model, 33% normal control and 83% EEVZ (100 mg/kg) animals were alive, while 100% protection was achieved in standard drug phenobarbital (20 mg/kg), EEVZ (200 mg/kg) and EEVZ (400 mg/kg) animals. Discussion and conclusion: Findings demonstrate that V. zizanioides shows significant anticonvulsant activity in mice.